Дискретна інтерполяція спіралеподібних дискретно представлених кривих на основі нелінійного закону зміни кутів суміжності - Мацулевич, Олександр Євгенович; Михайленко, Олена Юріївна; Супрун, Максим Володимирович; Matsulevych, Oleksandr; Mykhailenko, Olena; Suprun, Maksym (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Дослідження зосереджено на проблемі інтерполяції дискретно представлених кривих (далі – ДПК), зокрема спіралей та замкнених контурів. Представлено нелінійну формулу для зміни кутів суміжності під час згущення спіралеподібних ДПК, яка випливає з підтвердженої тотожності, що пов’язує кути до й після процесу ущільнення. Шляхом накладання додаткових умов на співвідношення кутів розроблено різноманітні різницеві алгоритми. Вони гарантують відмінну розрахункову точність і повністю виключають осциляції згущеного контуру. Крім того, розроблено й теоретично підтверджено спосіб згущення, що базується на геометричних залежностях між кутами суміжності. Перевага цього способу полягає в його рівномірній ефективності як на опуклих сегментах, так і на перехідних зонах з можливістю відстежувати точки перетину. /// EN: Experimental scientific research, as well as solving practical problems of modeling various types of channel surfaces of internal combustion engines and their flat cross-sections, pose many requirements. The geometric model and calculation algorithms must be simple, taking into account an arbitrary number of specified conditions, and ensuring the possibility of local changes in the shape of a curved line or surface without oscillation. Existing and known methods are not able to fully meet these requirements. The problem can be solved within the framework of discrete geometric modeling (DGM). Solving these problems using discrete geometric modeling, one of the directions of which is discrete interpolation (condensation). Known DGM methods allow all of the above problems to be solved, with the exception of ambiguous curves, for which the appropriate methods have not yet been developed. The research focuses on the problem of interpolation of discretely represented curves (DRC), in particular spirals and closed contours. A key element of the proposed approach is the analysis of the dynamics of angle changes between adjacent segments of a broken DPC line, which serves as the basis for forming the necessary set of angles for curve condensation. A nonlinear formula is presented for changing the angles of adjacency during the condensation of spiral-shaped DPCs, which follows from the confirmed identity linking the angles before and after the condensation process. Various difference algorithms have been developed by imposing additional conditions on the ratio of angles. These algorithms guarantee excellent calculation accuracy and completely eliminate oscillations of the condensed contour. In addition, a condensation method based on geometric dependencies between contiguity angles has been developed and theoretically confirmed. The advantage of this method is its uniform efficiency on both convex segments and transition zones with the ability to track intersection points. The practical significance of the results obtained in this work lies in improving the accuracy of modeling and reducing time and material costs by obtaining more sophisticated models. The proposed methods are intuitive and allow designers to achieve the desired result more quickly by correcting the shape. Condensation based on the proposed nonlinear law of change in adjacency angles when solving difference schemes obtained by imposing certain relationships between adjacency angles allows for a wide variety of solutions, among which the optimal one can be selected or constructed according to a specific criterion.
Discrete interpolation of spiral-like discreetly represented curves based on a nonlinear law of change of adjacency angles
Keywords: супроводжувальна ламана лінія; кут суміжності; кінцева різниця; спіралеподібна дискретно подана крива; accompanying broken line; angle of adjacency; terminal difference; spiral-shaped discretely represented curve